Mimesis in Emily Dickinson’s Select Poems: A Mirror Through Realities - AMPO, WEENA MAE (International Journal of Language and Literary Studies, 2022)
This paper aims to reveal the acceptance of life’s realities as expressed by the poet in her select poems through the lens of the mimetic theory of Rene Girard. Specifically, the mimetic significations are analyzed through each poem’s poetic vision. The literary study is a qualitative descriptive, it employs closed reading and content analysis methods to determine the poetic visions of the select poems: “Hope” is the thing with feathers,” “Because I could not stop for Death,” “If I can stop one heart from breaking,” and “I’m Nobody! Who Are You?” The analysis of poetic visions reveals that hope remains despite life’s struggles and difficulties; the acceptance of death is an eternity of living; compassion is a language of love, and fame brings complexity to life.